Pengaruh Tingkat Pendidikan, Pemahaman Akuntansi, dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Keuangan (Studi Kasus Pada Koperasi Se-Kabupaten Buleleng) - Putu Meliani; Desak Nyoman Sri Werastuti (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study was aimed to investigate the effect of educational level, accounting mastery level, and the use of information technology toward the Cooperatives financial reports quality in Buleleng Regency. The population of the study were 160 respondents that consist of the leaders and treasurers of the cooperative. The sampling method used in this study was purposive sampling method. The primary data were used in this study. Furthermore, the study used qualitative approach in the form of a Likert scale questionnaire. The data were analyzed by using multiple linear regression test in SPSS 24.0 for windows program. Individual educational level can affect the understanding of financial reporting. Seeing from the respondents’ responses, most of the cooperative's management have undergraduate education level, have good accounting understanding, and have used information technology maximally since the cooperatives have been supported by adequate information technology system. The results of the study show that the level of education, the accounting mastery level, and the use of information technology have a positive effect on the quality of financial reports. It indicates that the higher the level of education, the better accounting mastery, and the maximum used of information technology, the better of financial statements will be reported